Light Metals 2018 - Martin, Olivier (The Minerals, Metals & Materials Series, 2018)
The Light Metals symposia at the TMS Annual Meeting & Exhibition present the most recent developments, discoveries, and practices in primary aluminum science and technology. The annual Light Metals volume has become the definitive reference in the field of aluminum production and related light metal technologies. The 2018 collection includes papers from the following symposia: 1.Alumina and Bauxite 2.Aluminum Alloys, Processing, and Characterization 3.Aluminum Reduction Technology 4.Cast Shop Technology 5. Cast Shop Technology: Energy Joint Session 6. Cast Shop Technology: Fundamentals of Aluminum Alloy Solidification Joint Session 7. Cast Shop Technology: Recycling and Sustainability Joint Session 8. Electrode Technology for Aluminum Production 9. Perfluorocarbon Generation and Emissions from Industrial Processes 10. Scandium Extraction and Use in Aluminum Alloys .